Effect of Nickel Contamination on the Growth of Oleaginous Yeasts in Hydrolisates of Arundo Donax - Pirozzi, Domenico; Toscano, Giuseppe; Caputo, Gerardo; Florio, Ciro; Rugari, Felicia; Travaglini, Giuseppe; Yousuf, Abu; Zuccaro, Gaetano ("Gheorghe Asachi” Technical University of Iasi, Romania, 2015)
Hydrolysates of Arundo donax, a crop offering high productivity in contaminated orsalinized soils with no inputs of irrigation and agrochemicals, were used in a discontinuous fermenter to grow the oleaginous yeast Lipomyces starkey, to obtain microbial oils potentially useful for the production of 2nd-generation biodiesel. A mixture of fermentable sugars was obtained by steam-explosion and subsequent enzymatic hydrolysis of the lignocellulosic materials. The concentration of Ni2+ ions and of inhibitors of the microbial growth significantly affected both the biomass and the triglyceride yields. The microbial lipids produced were compatible with the synthesis of an automotive-grade biodiesel. A physico-mathematical model, developed todescribe the biomass growth, demonstratedthat the concentration of heavy metals affected the maximum biomass concentration,though its influence on the specific growthrate of the yeasts was not significant.